VD_FINDINFO MP / 2012 / 8 vom 25. April 2012 - VD Tribunal cantonal (2012)
DROIT D'AUTEUR ET DROITS VOISINS, INTÉGRITÉ DE L'OEUVRE, OEUVREDROIT D'AUTEUR | 1 al. 1 LDA, 11 LDA, 12 al. 3 LDA, 2 al. 1 LDA, 2 al. 2 LDA, 65 al. 1 LDA, 261 al. 1 CPC (CH), 261 CPC (CH)